Dens in Dente - Anita Balan; Nileena R Kumar; J Rema; Prasanth Balan (Wolters Kluwer Medknow Publications, 2006)
Dens in dente are developmental malformation resulting from invagination of the crown before it is calcified. This anomaly is most frequently found in the permanent maxillary lateral incisor. Three cases, one of radicular and two of coronal dens in dente are reported.